Hemichorea-Hemiballism as a Delayed Manifestation of Hyperglycemia: A Case Report. (January 2023) - Shivkumar, Vikram; Nemade, Dipali
Hemichorea is characterized by involuntary, continuous, non-patterned movements on one side of the body. While it is most commonly caused by strokes, it can also be caused by metabolic derangements such as hyperglycemia. We present two patients who developed hemichorea in the setting of hyperglycemia. Our first patient had a history of uncontrolled diabetes mellitus and developed chorea 2 weeks following a hyperglycemic event. The second patient developed chorea while being on steroids for hip pain and was later diagnosed to have underlying diabetes mellitus. MRI showed hyperintensity in the contralateral lentiform nucleus in both cases. The chorea did not improve despite the correction of the hyperglycemia. Both patients were started on Tetrabenazine with significant improvement. Hyperglycemia-induced hemichorea might be underdiagnosed given the prevalence of diabetes mellitus in the population. Chorea can even be the presenting symptom of diabetes mellitus and in some cases is a delayed manifestation of hyperglycemia.